The Role of Governments in Aligning Functional Income Distribution with Full Employment. Issue 3 (3rd July 2017) - Spithoven, Antoon
Abstract: Demand is an incentive for investment. The latter is necessary to create employment. If demand lags behind supply, then unemployment and underemployment rise. Persistent unemployment and underemployment indicate a dysfunctional price mechanism. Then, only governments can stimulate demand. They may equalize ex ante saving and investment by public investment, income redistribution, or market regulation.